Application of a three-dimensional printed pelvic model in laparoscopic radical resection of rectal cancer - Lu, Feng; Qiu, Lei; Yu, Peng; Xu, Da-Lai; Miao, Yong-Chang; Wang, Gang (Frontiers in Oncology, 2023)
To help understand the three-dimensional (3D) spatial relationships among the highly complex structures of the pelvis, we made a novel 3D pelvic model with a 3D printing system. We created some pelvic models including the muscles, vessels, nerves, and urogenital organs. The models clearly demonstrated the complicated spatial relationships between anatomical structures in the pelvis. Surgeons could use these models to improve their spatial understanding of pelvic anatomy, leading to improve the safety and efficiency in laparoscopic rectal cancer surgery.